Efektifitas Pemberian Perlakuan Posisi Miring Kiri dan Upright Position terhadap Percepatan Kemajuan Persalinan Kala I Fase Aktif pada Ibu Inpartu - Ijabah, Nizzatul; Achyar, Khamidah; Kusuma, Inggar Ratna (Jurnal Riset Kesehatan Masyarakat, 2023)
The World Health Organization (WHO) reports that every day in 2017, around 810 women die from problems or complications of pregnancy and childbirth that are preventable. One of the complications in childbirth is prolonged labor, analysis of data from the World Health Organization shows that in 2017 prolonged labor was the direct cause of labor complications with an incidence of 69,000 or 2.8% of all maternal deaths worldwide. This study aims to determine the effectiveness of giving treatment in the left oblique position and the upright position on the progress of labor in the active phase of the first stage of labor in giving birth mothers. This type of research uses a literature study or literature review with a descriptive research method. This study uses 2 databases, namely PubMed and Google Scholar. The strategy search method for obtaining journals uses the keywords "Effectiveness of Left Oblique Position on Labor Progress" or "Effect of Upright Position on Labor Progress" or "Labor Position Affecting Progress in the First Stage of the Active Phase". Furthermore, a screening of available titles, abstracts and full text was carried out on 1,180 articles and 15 articles were obtained that were suitable for inclusion and exclusion extraction. The results of the study obtained 15 literature that examined the effectiveness of labor positions to accelerate progress during the active phase. The conclusion of this study is that the left side position and the upright position affect the progress of labor in the first active phase of the mother giving birth.